FcRn Expression on Placenta and Fetal Jejunum during Early, Mid-, and Late Gestation in Minipigs. (April 2016) - Jacobsen, Björn; Hill, Marilyn; Reynaud, Lucie; Hey, Adam; Barrow, Paul
Developmental toxicity testing of therapeutic antibodies is most often conducted in nonhuman primates owing to lack of cross-reactivity in other species. Minipigs may show cross-reactivity for some humanized antibodies but have not been used for developmental toxicity testing due to an assumed lack of embryo-fetal exposure. Unlike in humans, maternal IgGs do not cross the porcine placenta to reach the fetus. Some humanized IgGs, however, have a higher affinity for the neonatal Fc receptor (FcRn) and are more likely than endogenous antibodies to cross the placenta of animals. The major site of prenatal IgG transfer is the placenta, though FcRn in fetal intestine could also uptake maternal IgGs from swallowed amniotic fluid. Using immunohistochemistry and in situ hybridization in this experiment, FcRn was found in minipig placenta and fetal intestine during early, mid-, and late gestation. To date, however, fetal exposure to maternally administered IgGs has never been demonstrated in the minipig.